Study on low pressure adsorption of biomethane from biogas by coal activated carbon - Wassana Kamopas (2018)
© School of Engineering, Taylor’s University. A study on low pressure adsorption of biomethane purified from biogas by a commercial coal activated carbon (AC) was carried out. The adsorption mechanisms of biomethane at 80 and 90% CH 4 concentration were considered by Langmuir model and Dubinin-Astakhov model. The lower biomethane concentration was better adsorbed since the activated carbon gave higher affinity for CO 2 than that for CH 4 . By Langmuir model, the limiting uptake of biomethane on the activated carbon (q max ) and the Langmuir’s constant (K L ) increased with the decrease of the AC temperature. The value of q max for 80% biomethane adsorption was in a range of 4.80-5.06 mmol/g (AC) compared with a range of 2.98-3.23 mmol/g (AC) for 90% biomethane adsorption. The value of K L was in a range of 0.37-0.43 MPa -1 . For Dubinin-Astakhov equation, the structural heterogeneity parameter (n) for the coal ACs was investigated and found to be 1.48. The isosteric heat of adsorption for 80 and 90% biomethane were in a range of 5.56-9.76 kJ/mol.